Governance and performance in public and non-profit organizations - Hinna, Alessandro; Gnan, Luca; Monteduro, Fabio (Studies in public and non-profit governance ;, 2016)
Studies in Public and Non-Profit Governance (SPNPG) publishes double-blind peer reviewed articles in a growing area of governance research. The series focuses on the 'micro' level of governance in public and non-profit sector. Compared to the wider debate on corporate governance in the private sector and to the literature on the 'macro' and 'meso' levels of governance in the public sector, the organizational (micro) level of governance remains a neglected area of governance in the public and non-profit sector. Therefore, governance systems, mechanisms and roles are primarily investigated at organizational level. SPNPG allows for the establishment of an engaged community of researchers very active in the field. It aims to contribute to the definition of the theoretical components that assign an innovation role to governance systems in public and non profit organizations. It also highlights the opportunity for a deeper analysis of governance mechanisms in their relationships with both the external (stakeholders) actors and the internal (management) actors and address the conditions which enable governance mechanisms to effectively cover their own roles.